Public Employment Services and Publicly Provided ALMPs in Egypt - Semlali, Amina; Angel-Urdinola, Diego F. (World Bank, Washington, DC, 2013)
This note presents a brief overview of Public Employment Services (PES) in Egypt and describes the institutional framework for public delivery of Active Labor Market Programs (ALMPs) in Egypt. Egypt has the fourth largest economy in the Middle East and North Africa (MENA) Region and has implemented economic reforms since 2004 which have led to some economic growth (e.g. a fast growing technology sector and the country has been recognized as one of the top offshoring destinations for international companies).